The Narrative of Abjection and Dissidence: Reading The Voice of Bhumika - Lama, Kumari (Khwopa Journal, 2023)
The paper explores the narrative of abjection and analyzes the voices of dissent portrayed in Bhumika Shrestha’s autobiography Bhumika: Autobiography of a Transgender (2018). Shrestha is a trans-woman, who suffers due to the established gender concept, normative heterosexuality and encounters consistent criticism, hatred and rejection from the society. Nonetheless, she dares to challenge the established social values and gender austerity. She rejects and resists against the patriarchal gender coding and struggles hard for her identity claim. She has been raising her voice for the rights of sexual and gender minorities since she got associated with Blue Diamond Society. To explore the established idea of gender and abjection, I have analyzed the life experience of Bhumika employing theoretical concept of Judith Butler that sheds light on the discriminatory concept of ‘liveable’ and ‘unliveable’ bodies in terms to sexual orientations.